2008
DOI: 10.3758/brm.40.2.428
|View full text |Cite
|
Sign up to set email alerts
|

Comparing online and lab methods in a problem-solving experiment

Abstract: 428The Internet has revolutionized the way in which people communicate and retrieve information. Powerful communication tools are transforming many scientific disciplines, including experimental and clinical psychology. The Web allows access to much wider populations-as well as to populations that were previously difficult to reach-in an inexpensive, fast, and convenient way. In clinical psychology, for example, psychological testing and assessment can be done online (see, e.g., Buchanan, 2002).In experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
113
2
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(142 citation statements)
references
References 21 publications
(18 reference statements)
13
113
2
5
Order By: Relevance
“…A number of studies have been conducted that compare the quality of data collected online with data collected through traditional lab procedures. Dandurand et al (2008) compared online and lab-collected data from a problem-solving experiment. Although online participants were less accurate in their study, the results were considered to be practically equivalent to those gained through lab experimentation.…”
Section: Online Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies have been conducted that compare the quality of data collected online with data collected through traditional lab procedures. Dandurand et al (2008) compared online and lab-collected data from a problem-solving experiment. Although online participants were less accurate in their study, the results were considered to be practically equivalent to those gained through lab experimentation.…”
Section: Online Data Collectionmentioning
confidence: 99%
“…As many experimental tasks are performed on computers, researchers have decided to administer studies using the Internet instead of having participants come to a lab (e.g., Snow et al, 2008;Suri & Watts, 2011). Although there are obvious concerns over diminished experimental control when experiments are run online, systematic efforts to compare data suggest that some kinds of HCI research can reliably be conducted with remote online participants (Dandurand, Shultz, & Onishi, 2008;Heer & Bostock, 2010;Komarov, Reinecke, & Gajos, 2013). However, these studies have tended to focus on simple tasks that can be completed relatively quickly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, both experiments suffered from high dropout rates, which is a common problem in online experimentation (Dandurand, Shultz, & Onishi, 2008). The dropout rates were higher in the QS experiment (88.1%) than they were in the CitSci experiment (74.57%) and the total number starting the QS experiment was over twice that starting the CitSci experiment (395 v 173 respectively).…”
Section: Conditionmentioning
confidence: 97%
“…We acknowledge that further research into this will be necessary to make stronger conclusions about this effect, although previous research has suggested differences in performance between labbased and online participants (Dandurand et al, 2008).…”
Section: Limitationsmentioning
confidence: 99%